SUSTAINABLE DEVELOPMENT REPORT OF THE ENTERPRISE: NECESSITY OF IMPLEMENTATION, ROLE AND PROBLEMATIC ASPECTS - PUKHALSKYI, Vadym (Scientific journal «World of Finance», 2026)
Вступ. Наприкінці XX століття з’явилася нова парадигма розвитку суспільства – сталий розвиток, яка набуває великого значення в сучасних умовах, коли питання збереження людства стоїть на першому місці. Поєднання трьох компонентів сталого розвитку (економічного, екологічного та соціального) має неабиякий вплив на розвиток суб’єктів господарювання будь-якої країни.Економічна компонента сталого розвитку важлива з погляду використання та збереження природних ресурсів. Екологічна націлена на збереження природного середовища та тривалість життя. Соціальна компонента передбачає досягнення таких життєвих стандартів, які прийнятні для людського існування.Мета – проаналізувати нормативні акти щодо складання, подання й оприлюднення звіту зі сталого розвитку суб’єктами господарювання України та виокремити позитивні і проблемні аспекти.Результати. Розглянуто концепцію звітності зі сталого розвитку з обґрунтуванням причин її запровадження, значення та проблемних аспектів. Проаналізовано законопроєкт “Про внесення змін до Закону України “Про бухгалтерський облік та фінансову звітність в Україні” щодо запровадження звітності із сталого розвитку”. Виокремлено низку проблем, що стосуються методики складання та проведення обов’язкового аудиту звіту зі сталого розвитку.Висновки. Уряд України робить усе можливе щодо імплементації CSRD та ESRS у забезпеченні відповідності законодавства України у сфері складання, подання й оприлюднення звіту зі сталого розвитку. Як результат, на українських суб’єктів господарювання очікує трансформація звітності, яка має відкрити можливість залучати в більших обсягах європейські інвестиції, виходити на європейські ринки капіталу, отримувати якісну й неупереджену інформацію з метою оцінювання екологічних і соціальних аспектів та оцінки їх впливу на навколишнє середовище. Introduction. At the end of the 20th century, a new paradigm of social development emerged – sustainable development, which is of great importance in modern conditions, when the issue of preserving humanity is in the first place. The combination of three components of sustainable development (economic, environmental and social) has a significant impact on the development of economic entities of any country.The economic component of sustainable development is important in terms of the use and conservation of natural resources. The environmental component is aimed at preserving the natural environment and prolonging life. The social component involves achieving living standards that are acceptable for human existence.The purpose of the article is to analyze regulatory acts concerning the preparation, submission and publication of sustainability reports by Ukrainian businesses and to highlight positive and problematic aspects.Results. The concept of sustainable development reporting is considered, with justification of the reasons for its introduction, significance, and problematic aspects. The European legislation and the draft Law of Ukraine “On Accounting and Financial Reporting in Ukraine” regarding the introduction of sustainable development reporting was conducted, which showed that it is mandatory to prepare, submit, and publish a sustainable development report together with an audit opinion. A number of issues have been identified that need to be addressed in the near future, primarily concerning the methodology for compiling and conducting mandatory audits of sustainability reports.Conclusions. Thus, the Ukrainian government is doing everything possible to implement CSRD and ESRS in ensuring the compliance of Ukrainian legislation in the field of preparing, submitting, and publishing sustainability reports. As a result, Ukrainian businesses can expect a transformation in reporting, which should open up opportunities to attract more European investment, enter European capital markets, and obtain high-quality and unbiased information for the purpose of assessing environmental and social aspects and their impact on the environment. At the same time, we have identified a number of unresolved issues that need to be addressed in the near future.